Analysis of typological structures of situational efficiency in judo female junior competitors - Kajmovic, H.; Rado, I.; Kapo, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Efficient action of judo for female juniors comperitors, cannot be described as uncontrolled or unorganised, in the same manner as it is not possible that at a certain moment all these typological indicators are maximised at the same time (Kajmovic at al., 2007). This research is intended to establish typological situational judo structures for female competitors, is focused on achievement of scientific fact which will have permanent character and which will be used in future as a solid ground for resolution of particularly applicative task in judo. Therefore, the problem and the subject of this work is clearly articulated, and is related to establishment of rules existing at the latent level of situational action in judo, for female competitors. Innovative technique in this work defines as entities the fights and not individual fighters, simply since in this way one can gain more detailed information on existing rules as well as interactions. Methods For the purpose of this work the sample used was 126 junior female competitors from 38 European countries, in all weight categories, coming up to 179 fights between female competitors at European championship U-20 for juniors held in Sarajevo, 2003. Each competitor was described with 133 parameters out of which, after the elimination of such variables with exclusively zero values, there were 74 left. Initial results were carefully recorded through watching of VHS tapes, what made the situational aspect of the research really credible. Results The data processing was performed in such a way which allowed production of useful information at all levels of analyses multi-variant complex models, in which a special place belongs to relation model of action. Results of this research give us the right to see the situational efficiency of judo female competitors comprises one latent dimension, which is separate in: a) tactical action b) global and strategic action, and c) action focused on technical segment. Discussion Understanding is seen in the possibility of recognition of isolated latent action mechanisms in situational aspect. Through this the research involves interpretability and repetitiveness, as well as the possibility to compare the results with other patterns and populations. This situational model is composed out of individual building elements representing the wish to win, the knowledge of conditions of realisation of activity and accumulation of efficient actions. A special segment to this theoretical model is added by the fact that the judo fighter has to have a precisely combined match which will give as a result a maximisation of each individual structural element.